2023
DOI: 10.26607/ijsl.v25i1.131
|View full text |Cite
|
Sign up to set email alerts
|

Estimating lighting device inventories with the LANcube v2 multiangular radiometer

Abstract: This paper is a technical report describing the use of an open source instrument called LANcube v2 to estimate a lighting devices inventory. The LANcube v2 is and instrument having 5 color sensitive sensors, each on a face of a cube. The instrument can be mounted on a car roof in order to create a map of the artificial light at night while roaming the streets and roads. Based on the temporal variations of the detected signal on various cube’s faces, we developed a method of finding the approximate position in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The LAN3V2 photometer is a relatively new ground-based instrument which offers a unique capability of measuring night-time brightness in three spectral bands and in five directions, thus allowing to map artificial lights and their colors and related light pollution indices over a wide area [22]. Working in a rural area, Aubé and Houle [26] demonstrated that using its multidirectional measurements, it was possible to map street light inventories in two small villages. In this paper, we examined the variability in night-time lights (both brightness and color) as measured by the LAN3V2 to better understand the factors affecting it and its correspondence with spaceborne measurements of night lights, as measured by the SDGSAT-1 [7]-the first multispectral spaceborne sensor offering acquisition of night-time lights at a medium spatial resolution as suggested in 2007 [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LAN3V2 photometer is a relatively new ground-based instrument which offers a unique capability of measuring night-time brightness in three spectral bands and in five directions, thus allowing to map artificial lights and their colors and related light pollution indices over a wide area [22]. Working in a rural area, Aubé and Houle [26] demonstrated that using its multidirectional measurements, it was possible to map street light inventories in two small villages. In this paper, we examined the variability in night-time lights (both brightness and color) as measured by the LAN3V2 to better understand the factors affecting it and its correspondence with spaceborne measurements of night lights, as measured by the SDGSAT-1 [7]-the first multispectral spaceborne sensor offering acquisition of night-time lights at a medium spatial resolution as suggested in 2007 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Ground measurements of night-time brightness as part of remote sensing studies have often used sky quality meters (SQM; [17,28,30]) or lux meters [28,38], such as the LAN3V2 [22,26], for calibration and validation purposes. While both approaches are valid, one of the main differences between them relates to the sensitivity threshold of illuminance meters vs. that of the SQM.…”
Section: Discussionmentioning
confidence: 99%